A Formative Experiment to Align Middle-School History Instruction with Literacy Goals. Issue 12 (December 2016) - Colwell, Jamie; Reinking, David
Background/Context: Recent curricular trends based on new standards emphasize the centrality of reading and studying texts in history instruction. That trend suggests a closer alignment between middle-school history instruction and goals for developing literacy. Yet potential obstacles identified in the literature, particularly a teacher's stance toward teaching history, imply challenges to instantiating that alignment. Relatively little research has addressed how relevant conceptual positions such as disciplinary literacy might be realized in authentic practice. Purpose/Objective: The objective was to investigate how middle-school history instruction could be transformed to align with the literacy goals addressed in new curricular standards and to better understand within a typical instructional context the pedagogical influences and outcomes associated with such a transformation. The intent was to lay the groundwork for an emerging pedagogical theory that could guide efforts to align history instruction and literacy goals. Intervention/Program/Practice: The researchers and the teacher collaboratively planned the instructional intervention that entailed three essential elements: (a) reading primary and secondary historical texts, (b) scaffolding strategies for reading such texts, and (c) writing blog reflections about readings. The teacher implemented the intervention in five topical history units taught during 10 consecutive weeks. Research Design: We employed a formative experiment to determine what factors enhanced or inhibited the intervention's success in achieving its aim, how it could be modified in light of those factors, what unanticipated outcomes were observed, and the extent to which the teaching and learning environment was transformed. Data Collection and Analysis: We collected qualitative data from multiple sources. During the intervention, we used an embedded case study to frame data collection and analysis. We conducted a retrospective analysis after the intervention phase in order to generate pedagogical assertions as a first step in establishing an emergent pedagogical theory. Conclusions/Recommendations: Three key assertions emerged that mediated the teacher's efforts to align her history instruction with literacy goals: (a) the influence of her beliefs grounded in her previous, imagined, and enacted practice; (b) blogging as a motivational catalyst; and (c) instructional enhancements that occurred when she observed the intervention's positive effects on achieving her pedagogical goals for students. These assertions comprise an emerging theory of how history instruction might be aligned with literacy goals and, as such, inform the literature on disciplinary literacy and how it might be achieved in authentic practice.